2019
DOI: 10.1177/0300060519878087
|View full text |Cite
|
Sign up to set email alerts
|

Primary closure with knotless barbed suture versus traditional T-tube drainage after laparoscopic common bile duct exploration: a single-center medium-term experience

Abstract: Objective: Primary closure of the common bile duct (CBD) after laparoscopic CBD exploration (LCBDE) is a technical challenge. The present study was performed to evaluate the safety and effectiveness of this surgical method. Methods: This retrospective study of surgical efficacy and safety involved 79 patients who underwent primary CBD closure with a knotless unidirectional barbed suture or traditional T-tube drainage after LCBDE for CBD stones. Results: The average suturing time, operation time, and postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Our study found that patients with the PDC had shorter operative and choledochotomy closure times than those with the TTD and ABS with an insignificant difference. Our results were consistent with several studies [ 9 , 13 , 25 , 35 , 41 , 45 ]. The long operative time in the ABS group was attributed to the time used for confirmation of stent position in the duodenum which was very crucial to guard against specific stent complications.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our study found that patients with the PDC had shorter operative and choledochotomy closure times than those with the TTD and ABS with an insignificant difference. Our results were consistent with several studies [ 9 , 13 , 25 , 35 , 41 , 45 ]. The long operative time in the ABS group was attributed to the time used for confirmation of stent position in the duodenum which was very crucial to guard against specific stent complications.…”
Section: Discussionsupporting
confidence: 94%
“…We agree with Deng et al [ 14 ] that this low incidence results from mandatory intraoperative confirmation of CBD clearance by cholangiogram and choledochoscope. Our study revealed no statistically significant difference among the 3 groups, and this was consistent with several studies [ 9 , 11 , 13 , 14 , 41 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, clinical studies have shown that T tube drainage has disadvantages including tube blockage, tube slip and long retention time, even causes infection of the skin or soft tissues. Most importantly, the integrity of the common bile duct is ruined, which will lead to bilary leakage ( 7 , 11 , 15 ). Therefore, it's crucial to choose an appropriate bile drainage method for the patients.…”
Section: Discussionmentioning
confidence: 99%